Operating Expenses Ratio (OER) and Total Asset Turnover (TATO) to Return on Assets (ROA) - Putri, Reyningrum Camilda; Pardistya, Irvan Yoga; Liana, Siska (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This quantitative study investigates the